Cationic Copolymerization of Styrene and C5 Refinery Stream with Et3NHCl-AlCl3 as Catalyst - Wang, G.Q.; Zhang, W.X.; Liang, J.C.; Chen, G.Y.; Wei, Z.Y.; Zhang, Long (Asian Journal of Chemistry, 2013)
The cationic copolymerization of styrene and C5 refinery stream with ionic liquid (Et3NHCl-AlCl3) as catalyst was reported in this paper. Effects of polymerization conditions on the softening point and colour were investigated. Et3NHCl-AlCl3 catalyst improved the colour of resin compared with AlCl3 and minimising process waste water production. The use of styrene futher improved the colour of resin. The optimum reaction conditions for this reaction are as follows: wstyrene = 20 %; solvent: CHCl3; m(Et3NHCl-AlCl3) = 2.6579 g; X(AlCl3) = 0.69; T = -5 ºC.